2022
DOI: 10.1093/ajhp/zxac130
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of a virtual interview process for pharmacy residents during the COVID-19 pandemic: A multisite survey of residency candidates, preceptors, and residency program directors

Abstract: Disclaimer In an effort to expedite the publication of articles related to the COVID-19 pandemic, AJHP is posting these manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…1,2 We agree that there are benefits to virtual recruitment, as evidenced by the cited work. 3,4 However, the decisions on whether to move to virtual versus hybrid versus onsite residency recruitment and interviews postpandemic are complex and multifactorial. Because we are still acclimating in this post-pandemic world, it may not be feasible to go back to a "one-size-fits-all" approach.…”
mentioning
confidence: 99%
“…1,2 We agree that there are benefits to virtual recruitment, as evidenced by the cited work. 3,4 However, the decisions on whether to move to virtual versus hybrid versus onsite residency recruitment and interviews postpandemic are complex and multifactorial. Because we are still acclimating in this post-pandemic world, it may not be feasible to go back to a "one-size-fits-all" approach.…”
mentioning
confidence: 99%
“…1 In contrast, Beechinor et al found a majority of programs preferred virtual interviews. 2 Benefits of virtual interviews were identified by both studies including reduced cost, anxiety, and time, and increased flexibility. 1,2 Alternatively, onsite interviews reduce technology issues, allow practice site tours, and increase socialization.…”
mentioning
confidence: 99%
“…2 Benefits of virtual interviews were identified by both studies including reduced cost, anxiety, and time, and increased flexibility. 1,2 Alternatively, onsite interviews reduce technology issues, allow practice site tours, and increase socialization. 1,2 Advantages of virtual interviews, namely, reduced cost (estimated >$1000/applicant), 2 benefit applicants significantly.…”
mentioning
confidence: 99%
See 2 more Smart Citations